2013
DOI: 10.1242/jeb.085779
|View full text |Cite
|
Sign up to set email alerts
|

Insulin-like peptides (AmILP1 and AmILP2) differentially affect female caste development in the honey bee (Apis mellifera)

Abstract: SUMMARYThe food a honey bee female larva receives determines whether she develops into a large long-lived fertile queen or a short-lived sterile worker. Through well-established nutrient-sensing and growth-promoting functions in metazoans, the insulin/insulin-like growth factor 1 signaling (IIS) pathway has become a focal topic in investigations on how differences in food environment can be translated into internal signals responsible for queen-worker determination. However, low expression levels of two insuli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
40
0
3

Year Published

2015
2015
2018
2018

Publication Types

Select...
4
4

Relationship

1
7

Authors

Journals

citations
Cited by 53 publications
(46 citation statements)
references
References 78 publications
(135 reference statements)
1
40
0
3
Order By: Relevance
“…1E, Table S2), consistent with the notion that transcriptional reprogramming of reproductive and neuronal function accompanies the worker–gamergate behavioral transition. Genes previously reported to be caste-specific in other social insects were also differentially expressed in Harpegnathos workers and gamergates, including several components of the insulin pathway (Daugherty et al, 2011; Libbrecht et al, 2013; Wang et al, 2013) ( Ilp1 , Ilp2 , InR1 , chico, hopscotch ) and energy storage proteins (Martins et al, 2011; Martins et al, 2010; von Wyschetzki et al, 2015) ( Hex70a , Hex70b, NLaz ) (Table S1). Genes involved in neurotransmission, such as those encoding GABA receptors Grik1 and Grik2 , as well as genes implicated in dendrite and synapse remodeling such as Fd3F (Parrish et al, 2006), Sulf1 (Dani et al, 2012), and Daw (Serpe and O’Connor, 2006) were also differentially expressed after the behavioral transition.…”
Section: Resultsmentioning
confidence: 87%
“…1E, Table S2), consistent with the notion that transcriptional reprogramming of reproductive and neuronal function accompanies the worker–gamergate behavioral transition. Genes previously reported to be caste-specific in other social insects were also differentially expressed in Harpegnathos workers and gamergates, including several components of the insulin pathway (Daugherty et al, 2011; Libbrecht et al, 2013; Wang et al, 2013) ( Ilp1 , Ilp2 , InR1 , chico, hopscotch ) and energy storage proteins (Martins et al, 2011; Martins et al, 2010; von Wyschetzki et al, 2015) ( Hex70a , Hex70b, NLaz ) (Table S1). Genes involved in neurotransmission, such as those encoding GABA receptors Grik1 and Grik2 , as well as genes implicated in dendrite and synapse remodeling such as Fd3F (Parrish et al, 2006), Sulf1 (Dani et al, 2012), and Daw (Serpe and O’Connor, 2006) were also differentially expressed after the behavioral transition.…”
Section: Resultsmentioning
confidence: 87%
“…Studies in Drosophila indicate that ILPs in the brain are involved in regulating carbohydrate metabolism and blood sugar titers [9,44]. In adult honey bees that an ILP ('AmILP1') gene expression is linked with blood sugar levels [55]. In decapod crustaceans, hyperglycemia occurs after stressful conditions by crustacean hyperglycemic hormone [56].…”
Section: Discussionmentioning
confidence: 99%
“…The genes whose expression differs between workers and queens in early stages are consistently expressed in this way throughout larval development (Cameron et al, 2013). These studies have identified a range of components including Hexamerins (Cameron et al, 2013), insulin-like peptide (Wang, Azevedo, Hartfelder, & Amdam, 2013), and mTOR (Patel et al, 2007), as playing key roles in the process.…”
Section: Developmental Plasticity In Larval Honeybeesmentioning
confidence: 99%
“…To determine the role of these genes requires manipulating gene expression during larval rearing in the lab, to see if development can be biased toward or away from queen development by knocking down the expression of a gene. Few studies have achieved this, but RNAi has been used to knock down Hexamerins (Cameron et al, ), ecdysone receptor (Mello et al, ), mTOR (Patel et al, ), insulin‐like peptide genes (Wang et al, ), and DNA methyl transferase 3(DNMT3) (Kucharski, Maleszka, Foret, & Maleszka, ). This last experiment showed that reducing DNA methylation, by knocking down DNMT3, reduces the ability to make workers during larval development, implying DNA methylation plays a major role in worker development (Kucharski et al, ).…”
Section: Introductionmentioning
confidence: 99%